Modification of PEG reduces the immunogenicity of biosynthetic gas vesicles - Wang, Yuanyuan; Fu, Meijun; Yang, Yaozhang; Zhang, Jinghan; Zhang, Zhaomeng; Xiao, Jingling; Zhou, Yingjie; Yan, Fei (Frontiers in Bioengineering and Biotechnology, 2023)
Nanobubbles have received great attention in ultrasound molecular imaging due to their capability to pass through the vasculature and reach extravascular tissues. Recently, gas vesicles (GVs) from archaea have been reported as acoustic contrast agents, showing great potential for ultrasound molecular imaging. However, the immunogenicity and biosafety of GVs has not yet been investigated. In this study, we examined the immune responses and biosafety of biosynthetic GVs and polyethylene glycol (PEG)-modified GVs (PEG-GVs) in vivo and in vitro. Our findings suggest that the plain GVs showed significantly stronger immunogenic response than PEG-GVs. Less macrophage clearance rate of the RES and longer circulation time were also found for PEG-GVs, thereby producing the better contrast imaging effect in vivo. Thus, our study demonstrated the PEG modification of biosynthetic GVs from Halobacterium NRC-1 is helpful for the future application of GVs in molecular imaging and treatment.